Analisis Sistem Akuntansi Anggaran Biaya pada Jawara Coffee Shop - Novita, Aliya Putri; Fatmanegara, Fahmi; Samuela, Joeanna Talita; Mutakin, Manarul Iza; Fauziyah, Fauziyah (Balance: Media Informasi Akuntansi dan Keuangan, 2024)
The purpose of this research is to perform a cost analysis of Jawara Coffee Shop's Production Budget. This Research method includes Production cost data collection, including materials, workers' wages, operational costs, and other relevant variables. The research result will offer detailed information regarding production budget effectiveness in managing and controlling operational costs at Jawara Coffee Shop. This discovery focuses on specific aspects of the costing that need improvements or adjustments. In this context, the researcher also gives recommendations for a cost adjustment strategy to support Jawara Coffee Shop's growth. This analysis will offer a profound understanding of production cost components and offer a strategic perspective to increase the operational efficiency of Jawara Coffee Shop in the future.